Long-term outcomes of tympanoplasty with persistent air-bone gap in adults with chronic otitis media: hearing, health care utilization and quality of life - Arndt, Susan; Deguine, Olivier; Nevoux, Jérôme; Sánchez, Serafin; Yılmaz Topçuoğlu, Miray-Su; D’hondt, Christiane; Hua, Håkan; Lin, Ray; Altuna, Xabier (European archives of oto-rhino-laryngology and head & neck, 2025)
To evaluate long-term hearing outcomes, healthcare utilization, and health-related quality of life (HRQoL) in adults with chronic otitis media (COM) who underwent primary tympanoplasty (PT) but were left with a significant air-bone gap (25-30 dB).